Fault Structure Analysis Using GGMPlus Satellite Gravity Data in Sumenep Regency, East Java for Disaster Mitigation - Neila Ayuzita Azhalia; Muwardi Sutasoma; Adi Susilo; Mohammad Habibiy Idmi; Rosita Wijayanti; Yanti Boimau (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2026)
Sumenep Regency is an area that has experienced earthquakes with fatalities caused by activity along the Rembang, Madura, Kangean, and Sakala (RMKS) faults. This study aims to identify subsurface structures, particularly faults, in the Sumenep region using satellite gravity image data downloaded from GGMPlus. The gravity acceleration data obtained were processed into Complete Bouguer Anomalies (CBAs) and separated into regional and residual anomalies using a Butterworth filter. Then, First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) analyses were performed to clarify the anomaly boundaries and subsurface structures. Next, 2D geological modeling was performed on the residual anomaly data to determine the types and boundaries between subsurface formation layers. The results of the study showed significant variations in gravity anomalies, with high contrasts in the southwest and southeast areas, indicating differences in the density of subsurface rocks. FHD and SVD analyses successfully delineated suspected faults, especially in areas with contact layers between low-and high-density rocks. The 2D modeling showed that the contact layer between the Ngrayong-Tawun Formation and the Ngrayong-Bulu Formation has a weak bond, making it more vulnerable to triggers such as earthquakes. These results emphasize the importance of further study and disaster mitigation related to active faults in the region. For future research, it is necessary to conduct field surveys and integrate them with other geophysical methods to improve the accuracy of the results.